CD151 in Respiratory Diseases - Wong, Amanda H.; Tran, Thai (Frontiers in Cell and Developmental Biology, 2020)
The tetraspanin, Cluster of Differentiation 151 (CD151), is ubiquitously expressed in adult tissue, especially in the lungs where it has been implicated in lung cancer, asthma, influenza, and idiopathic pulmonary fibrosis (IPF). CD151 interacts with laminin-binding integrins and growth factor receptors, and is reported in cancer-promoting processes such as tumor initiation, metastasis, and angiogenesis. In asthma, CD151 was shown to promote airways hyperresponsiveness through calcium signaling whereas in influenza, CD151 was shown to be a novel host factor for nuclear viral export signaling. Furthermore, CD151 was shown to be associated with increased disease severity and poorer survival outcome in asthma and lung cancer, respectively. In this review, we provide an update on the current understanding of CD151 with regards to its contribution to lung pathophysiology. We also summarize factors that have been shown to regulate CD151 expression and identify key areas that need to be taken into consideration for its utility as a screening or prognostic tool in disease management and/or as a therapeutic target for the treatment of lung diseases.